P-685 Optimal aspiration pressure level of suction pump for oocyte retrieval in IVF-ET. (30th June 2022) - Kim, T; Kang, M.J; Han, S.J; Kim, S.W; Kim, H; Ku, S.Y; Suh, C.S
Abstract: Study question: What is the appropriate suction pump pressure for oocyte retrieval in terms of oocytes and embryos quality? Summary answer: The aspiration pressure of 150mmHg had a significantly higher number of oocytes retrieved compared with 120mmHg, but the oocyte quality and embryo quality were comparable. What is known already: There is no conclusion on the optimal aspiration pressure level for oocyte retrieval in controlled ovarian stimulation (COS), and a variety of pressures between 100 and 200 mmHg are used, often based on manufacturer's instructions. Study design, size, duration: A retrospective analysis was performed on a total of 211 COS cycles from September 2019 to December 2021 in a single tertiary center. The analysis was performed on patients who underwent COS for the purpose of infertility treatment. Participants/materials, setting, methods: 110 cycles were included in the 120 mmHg pressure group and 101 cycles were included in the 150 mmHg pressure group. Age, AMH, antral follicle count (AFC), the proportion of ICSI, the number of retrieved oocytes, the number of MII oocytes, MII rate, degeneration rate on day 1, and the number of embryos on day 3 were compared between the two groups. Variables such as Age, AMH, and AFC were corrected using analysis of variance. Main results and the role of chance: The number of retrieved oocytes was significantly higher in the 150 mmHg group compared to the 120 mmHg group (10.3 vs. 8.4, p = 0.016). Neither the number of MII oocytes nor the MII rate was significantly different between the two groups (6.1 vs. 5.5, p = 0.509 and 67.2% vs. 73.4%, p = 0.437 respectively). The degeneration rate on day 1 and the number of embryos on day 3 were also not significantly different between the two groups (6.2% vs. 4.4%, p = 0.282 and 5.7% vs. 4.7%, p = 0.109 respectively). Limitations, reasons for caution: Since this study analyzed the appropriate pump pressure for oocyte retrieval in infertile patients, caution is needed in extending the study results to patients undergoing oocyte retrieval for the purpose of fertility preservation. Wider implications of the findings: The results of this study revealed that oocyte collection could be efficiently performed without damaging the oocytes even with a higher aspiration pressure of 150 mmHg. Trial registration number: Not applicable